Ljubljana - faze urbanega razvoja - Jakoš, Aleksander (Urbani izziv, 2006)
At the end of the Second World War there were approximately 100.000 people living in the compact part of Ljubljana. A period of rapid population development ensued (urbanisation) because of immigration from other parts of Slovenia and later from various regions of the former Yugoslav Republics. Thisperiod is marked by numerous new housing estates and early stagnation of the old city core. A period ob sub-urbanisation followed and city expansion along the main roads, interspersed with poor quality building and illegal development. Costly renewal of old buildings, diminished construction of housing estates and high prices of building land triggered the flight of city dwellers (de-urbanisation) and caused non-urban development in neighbouring municipalities (secondary urbanisation). By rehabilitation of the old city centre and attempts at revitalisation Ljubljana is trying re-urbanise itself. The flight of the younger population, caused by limited offer of housing, still remains the main problem that furthermore causes increased volumes of daily commuting and congestion in the city centre caused by parked vehicles. The tally of increased population during the last decade to small neighbouring municipalities, caused by flight from Ljubljana, is 20.000, while the population of Ljubljana is decreasing. With its quarter of a million inhabitants, Ljubljana is the third smallest capital city of Europe (without the "pocket" states). The main issue in the neighbouring municipalities is expressively non-urban development, meaning that too much land is used and theutilities infrastructure threshold is not met. The present division of the Ljubljana metropolitan region truly calls for a Strategy of spatial development, at least on the level of the Ljubljana urban region.
Keywords: demografski razvoj; Ljubljana; obmestja; suburbanizacija; urbani razvoj; urbanizacija